2016
DOI: 10.2298/bah1601015k
|View full text |Cite
|
Sign up to set email alerts
|

Plasma hormones and milk production performances in early lactation buffaloes supplemented with a mixture of prilled fat, sweetener and toxin binder

Abstract: The effect of combined feed supplements (prilled fat, sweetener and toxin binder) was studied on 24 apparently healthy early lactating rural and urban maintained Murrah buffaloes. The feeding of combined feed supplement was carried out for a period of 90 days. DMI, BCS, body weight were recorded at fortnightly intervals and milk composition was analyzed at weekly intervals. Blood samples were analyzed for hormones, plasma metabolites and lipid profile. The supplementation increased (p<0.01… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Similar observations have been reported earlier by Tyagi et al (2010) and Savsani et al (2013). However, greater values of blood glucose on supplementation of high energy diet were reported in buffaloes by Campanile et al (2010) and Khan et al (2016). Funston et al (1995) reported that fat supplementation may increase glucose production through increased propionate production and this increase in glucose may have a positive effect on LH release.…”
Section: Blood Glucosementioning
confidence: 92%
“…Similar observations have been reported earlier by Tyagi et al (2010) and Savsani et al (2013). However, greater values of blood glucose on supplementation of high energy diet were reported in buffaloes by Campanile et al (2010) and Khan et al (2016). Funston et al (1995) reported that fat supplementation may increase glucose production through increased propionate production and this increase in glucose may have a positive effect on LH release.…”
Section: Blood Glucosementioning
confidence: 92%
“…According to Campanile et al [109], buffalo heifers fed with Brachiaria hay and supplemented with concentrate (high-energy diet) showed increases in GH and IGF-1 levels compared to buffalo fed with a basal diet without concentrate (low-energy diet) (6.3 vs. 5.6 pg/mL, 95.5 vs. 79.1 ng/mL, respectively). Other studies also revealed that Murrah buffalo increased IGF-1 and remain constant in GH levels when fed a diet supplemented with a mixture of concentrate with bypass fat when compared to being fed with a diet supplemented solely by concentrate (119.10 vs. 116.24 ng/mL, 4.91 vs. 4.93 ng/mL, respectively) [113,133]. Even though a few studies have shown the effects of dietary fat and protein supplements on the serum biochemistry profiles as well as the hormonal profiles in the blood, unfortunately, limited work has been performed on the comparison of blood and hormonal profiles between buffalo breeds.…”
Section: Serum Biochemistry and Hormone Profilesmentioning
confidence: 99%